2004
DOI: 10.1002/jez.b.21020
|View full text |Cite
|
Sign up to set email alerts
|

Status of RNAs, localized in Xenopus laevis oocytes, in the frogs Rana pipiens and Eleutherodactylus coqui

Abstract: Early development in the frog model, Xenopus laevis, is governed by RNAs, localized to the vegetal cortex of the oocyte. These RNAs include Xdazl RNA, which is involved in primordial germ cell formation, and VegT RNA, which specifies the mesoderm and endoderm. In order to determine whether orthologues of these RNAs are localized and have similar functions in other frogs, we cloned RpDazl and RpVegT from Rana pipiens, a frog that is phylogenetically distant from X. laevis. RNAs from both genes are localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…These findings demonstrated that the function of vegt as meso-endodermal determinant is conserved in frogs (16). The RNA localizations and functions of vegt orthologs in germ-layer specification may be synapomorphies for anuran amphibians (16).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…These findings demonstrated that the function of vegt as meso-endodermal determinant is conserved in frogs (16). The RNA localizations and functions of vegt orthologs in germ-layer specification may be synapomorphies for anuran amphibians (16).…”
mentioning
confidence: 73%
“…A high degree of vegt conservation was detected in these anurans (8). Moreover, when Ec_vegt or Rp_vegt mRNAs were injected into two-cell embryos of X. laevis, endodermal, mesodermal, and organizer genes were induced (16). These findings demonstrated that the function of vegt as meso-endodermal determinant is conserved in frogs (16).…”
mentioning
confidence: 74%
See 3 more Smart Citations